Distinguishing between religion and spirituality: Listening to teenagers within the (RCCG) Pentecostal Churches - Adebayo, R. (Journal of the European Pentecostal Theological Association, 2019)
This article investigates how teenagers in the Pentecostal Church, particularly the Redeemed Christian Church of God (RCCG), distinguish between religion and spirituality. In addition to presenting the findings of this study, the article compares the teenage participants’ perceptions of these constructs to the findings of previous researchers, including Overstreet [“Spiritual vs. Religious: Perspectives from Today’s Undergraduate Catholics.” Journal of Catholic Education 14, no. 2 (2010): 238–262], Smith and Denton (Soul Searching: The Religious and Spiritual Lives of American Teenagers. New York, NY: Oxford University Press, 2005) and others. The study was carried out among 27 teenagers, aged between 13 and 15, who attend the RCCG, which is one of the Pentecostal denominations in England. Critical analysis of the interpretation of religion falls into these categories: substantive and functional beliefs and practice, ordinary classification, and legalistic rules of do’s and don’ts. Similarly, spirituality falls into the categories of personal belief in and connection with God, the outward expression of religion, and mystical experience. Similar to the extant researchers, the majority of the participants made a clear distinction between religion and spirituality, while the remainder argued that the terms are too closely intertwined to draw a clear distinction between them. © 2018, © European Pentecostal Theological Association 2018.
Paid
Keywords: Black Majority Churches (BMCs); Pentecostal; Redeemed Christian Church of God (RCCG); Teenage; religion; spirituality